PROFITABILITY, SOLVENCY AND SELF-FINANCING OF THE FOOD AND BEVERAGE SECTOR IN COLOMBIA BETWEEN 2012-2015 - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
To analyze the behavior of profitability, solvency and self-financing in the Colombian food and beverage sector, a balanced and refined database of 2,639 companies was built in the period 2012-2015 that make their accounting reports annually before the Information and Information System Business Report - SIREM. By mathematical transformation, six indicators were generated (debt ratio, current liabilities, gross margin, return on assets - ROA, return on equity - ROE, and solvency). In general terms, the food and beverage sector are profitable, with a higher profit margin on its assets for the food business, which allows reinvestment and growth of the sector over time.